Distribution economics analysis of government interventions in poverty reduction amid the COVID-19 pandemic in Klungkung Regency, Indonesia - Marhaeni, AAIN; Sudibia, I Ketut; Tirtayani, I Gusti Ayu; Primajana, Dewa Jati (Journal of Economics and Business Letters, 2024)
Amid the pursuit of sustainable development goals in Indonesia, with a keen align- ment with the Sustainable Development Goals (SDGs), the pressing issue of poverty alleviation looms large. This study, set in Klungkung Regency, aims to comprehen- sively understand and address key facets of poverty alleviation during the COVID- 19 pandemic. The primary objective of this research is to investigate the impact of the COVID-19 pandemic on the depth of poverty in Klungkung Regency, Indone- sia. To achieve these objectives, our research involved the selection of 37 mainland Klungkung’s villages as our study area. We collected data from a diverse sample of 296 respondents, employing a combination of sampling methods, including acci- dental, snowball, and purposive sampling. Our findings reveal a significant increase in poverty levels among respondents attributable to the COVID-19 pandemic, with discernible variations across different sectors. Notably, agricultural laborers demon- strated greater resilience compared to their non-agricultural counterparts. Crucially, the government’s interventions emerged as pivotal, leading to an enhancement in purchasing capacity among beneficiaries. In terms of implications, this study un- derscores the critical importance of precisely targeted government interventions in poverty alleviation during crises. It highlights the need for policies that focus on both short-term relief and long-term economic stability.